True faith in the true God : an introduction to Luther's life and thought - Schwarz, Hans, 1939- (Minneapolis : Fortress Press, 2015)
True Faith in the True God meets the need for a clear and concise introduction to the life and teachings of the great church reformer, Martin Luther. After a brief overview of his life, the book devotes chapters to Luther's thoughts on several key areas of Christian faith and life, including the knowledge of God, church and sacraments, the Scriptures, marriage and parenthood, and vocation. Author Hans Schwarz incorporates quotations from Luther's own writings to show how Luther's insights have relevance for all Christians today.
Luther's life and work -- True knowledge of God -- Faith and reason -- The divinity of God -- Humanity between God and Satan -- The ordering activity of God (the Two Kingdoms) -- Scripture alone -- Law and Gospel -- Church and sacrament -- Love, marriage, and parenthood -- Vocation -- The impact on education -- Luther and the economy -- Luther and music.
Includes bibliographical references (pages 281-285).
Keywords: Luther, Martin, -- 1483-1546.; Reformation -- Biography